The analysis of the meaning of psychological terms or the behavioral analysis of psychological terms? - Zilio , Diego (Perspectivas em Análise do Comportamento, 2023)
In this essay I will present the contextualist theory of meaning proposed by Abib in his article “The contextualism of verbal behavior: Skinner’s theory of meaning and his criticism of the concept of reference”. I will argue that the contextualist theory of meaning is central to two distinct research programs which are often mixed together in behavior analysis. The first is the analysis of the meanings of psychological terms, which entails locating the controlling conditions of the use of psychological terms. The second is the behavioral analysis of psychological terms, which entails proposing interpretations of psychological categories in line with radical behaviorism philosophy. Even though Abib has emphasized the first research program in his 1994 article, he ended up dedicating himself exclusively to the second in his works. However, Abib is not alone in this: although behavior analysts recognize the importance of the first research program, they usually do research only in the second.